Rare earth elements affect the growth and fitness of free-floating plant Lemna minor L. - Gjata, Isidora; Tommasi, Franca; De Leonardis, Silvana; Paciolla, Costantino (Frontiers in Plant Science, 2025)
Rare earth elements (REEs) are increasingly utilized in modern technologies but are now recognized as emerging pollutants, with limited understanding of their impact on aquatic ecosystems. In this study, the effects of selected REEs (Ce, Nd, Gd, Dy, Yb, Ho, and Lu) in chloride form were evaluated on Lemna minor L., a plant species widely used as tool for the biomonitoring of the aquatic environments. Under controlled laboratory conditions, growth parameters, pigment content, oxidative stress markers, total antioxidant capacity, and antioxidant enzyme activities were assessed at millimolar concentrations over different exposure periods. L. minor exhibited tolerance to low millimolar concentrations of REEs over short-term exposure. However, prolonged exposure to high concentrations resulted in toxicity, characterized by growth inhibition, chlorophyll degradation, increased lipid peroxidation, and oxidative stress. Particularly, a hormetic response was observed for cerium, with stimulation at low concentrations and inhibition at higher levels, while dysprosium did not significantly affect growth. Other tested REEs induced varying degrees of stress, with holmium and lutetium causing the most severe toxic effects. Changes in antioxidant enzyme activities indicated a differential activation of stress responses depending on the REE type. These findings highlight the necessity for continuous monitoring of REEs in aquatic systems and support the use of L. minor as a valuable tool for environmental risk assessment.